Enriching surgical theatre competence through computer-based simulation. - Arruzza, E.; Chau, A.; Gomes, Y.; Philpot, M. (Radiography, 2025)
Radiographers support the multidisciplinary team by facilitating medical imaging within the operating theatre environment. This project aimed to enhance student readiness for clinical competency in operative theatre imaging by implementing an authentic C-arm simulator for students to use prior to attending clinical placement. This study followed a pre-post, quantitative study design. Medspace.VR© CA is a computer simulation software which allows users to produce radiographic images using a virtual 'C-arm' imaging scanner, within a 3D operating theatre environment. Educational workshops were followed by Likert-scale surveys to ascertain perspectives relating to student satisfaction, engagement, knowledge and skill enhancement, and reflections on behavioral changes following engagement with the simulator. The post-simulator survey demonstrated favourable scores were favourable in terms of student enjoyment (94 % agreed or strongly agreed), skill development (94 %), anatomical knowledge (63 %), operation of the machine (94 %) and its relevance to the radiographer's role (100 %) and professional capabilities (87 %). Most students found the program's instructions to be straightforward (81 %). Questions relating to confidence also demonstrated favourable results, with students highlighting perceived greater confidence in their abilities (87 %) and the theatre environment (61 %). When asked whether the C-Arm simulator is just as effective as hands-on placement experiences, 50 % of participants disagreed or strongly disagreed with this statement. The C-arm simulator enabled our students to engage in authentic, scenario-based cases within simulated settings, mirroring conditions encountered in clinical practice. Overall, the findings highlight positive levels of perceived development and satisfaction. Future studies should evaluate objective knowledge and skill development within the clinical setting. Simulator use in this context prior to clinical placements, has the potential to reduce anxiety, increase satisfaction and expedite skill acquisition.